(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
These research had shown a relationship between preparation and good academic population of teacher, and amelioration scientific level of schoolboy, because the teachers who had an academic population they have the capability which help theme to afford the lessons by activity and alacrity. So the teacher who has a good academic population, he will be revealed by education methods , and he know how to behave with schoolboys , and he also revealed by scientific material , and he can use the technology and the appliance of development, and the agents of education very well ,and suitable way, because when the teacher use too much agents of education in the lesson these maybe disperse the schoolboy attention, and it will be make his consideration on these agents only , but using the agents of education by suitable way it will be help the schoolboy to understand better, additionally the importance of advancement which the teacher give to schoolboy . these phraseology will encourage schoolboy to elevation there scientific level. And it was shown also there are a strong relationship between the way of cooperation and the scientific level of schoolboys, where the cooperation which depend on deference reverse a good relationship between teachers and schoolboys, and also between schoolboys themselves. Also it was noted there are a big difference between using the technology ,and the developments agents , and the computers by existence the teacher , and by using it without hem, where the teacher existence ,will be rise the schoolboys abandonment to learn.